The presence of Enterococcus faecalis in saliva as a risk factor for endodontic infection - Gaeta, Carlo; Marruganti, Crystal; Ali, Islam A. A.; Fabbro, Andrea; Pinzauti, David; Santoro, Francesco; Neelakantan, Prasanna; Pozzi, Gianni; Grandini, Simone (Frontiers in Cellular and Infection Microbiology, 2023)
Aim The aim of the present study was to investigate and correlate the prevalence of Enterococcus faecalis in saliva and in root canals with different pulpal and periapical conditions. Methodology Sixty-seven patients were divided into five groups based on pulpal and periapical tissue status: healthy vital teeth (HVT, n=7), healthy treated teeth without lesion (HTT, n=9), irreversible pulpitis (IP, n=13), necrosis (N, n=18), and post-treatment apical periodontitis (PTAP, n=20). Saliva, rubber dam, sterility control and pre-treatment root canal samples were collected and microbiologically processed by culture method. The phylogenetic relationship of E. faecalis isolates collected from root canals and saliva were investigated by whole genome sequencing. Fisher’s exact test was used to correlate the presence of E. faecalis in root canals or saliva with clinical and/or radiographic findings. Linear/logistic regression analyses were performed to establish the relationship between the presence of E. faecalis in root canals, saliva, and the status of periapical tissues. Results E. faecalis was found in 18 root canal and saliva samples. E. faecalis root canal isolates were recovered with the highest frequency from post-treatment apical periodontitis. The occurrence of E. faecalis in saliva was strongly associated with its detection in the root canals (P < 0.001). The pretreatment presence of E. faecalis in root canals was associated with significantly higher odds of having periapical lesions (OR=11.03; 95% CI, 1.27-95.70; p < 0.05). Saliva and root canal isolates from the same patient were highly correlated at the phylogenetic level (Jaccard index >0.95). Conclusion This pilot study confirms the role of E. faecalis in developing peri-radicular lesions in secondary endodontic infections and suggests that saliva could be the main source of infection. Further studies are needed to investigate the exact origin of this bacteria and its true role in the pathogenesis of secondary/persistent endodontic infections.